Case report: Recurrent pontine stroke and leukoencephalopathy in a patient with de novo mutation in COL4A1 - Zhang, Hui; Fan, Kai-Li; Zhang, Yue-Qi; Hao, Xiao-Yan; Yuan, Xiang-Zhen; Zhang, Shu-Yun (Frontiers in Neurology, 2023)
This report presents a case of pontine autosomal dominant microangiopathy with leukoencephalopathy (PADMAL) in a 35 year-old male patient. The patient exhibited a consistent history of recurrent ischemic strokes, concentrated primarily in the pons region, accompanied by concurrent manifestations of leukoencephalopathy and microbleeds. Genetic evaluation revealed a heterozygous missense mutation consistent with c.3431C>G, p. Thr1144Arg substitution within exon 40 of the COL4A1 gene. This mutation was also identified in the patient’s mother, affirming an autosomal dominant inheritance model. Our findings serve as testament to the potential role of mutation in the exon 40 of COL4A1 in the pathogenesis and progression of PADMAL, contributing to ongoing efforts aimed at better understanding the genetic basis of this debilitating disorder.